In Search of the Female Hobo - Tapley, Heather (Atlantis, 2009)
The following article questions the absence of the female hobo in American history. Focusing on narratives produced by self-identified hobos and hobo organizations of the late-nineteenth and early-twentieth centuries, the author contends that the female hobo is located in the deconstruction of discourses of hobo masculinity.